Prognostic Significance of Uric Acid in Patients with Obstructive and Nonobstructive Coronary Artery Disease Undergoing D-SPECT - Xu S (Dove Medical Press, 2021)
Siling Xu,1 Lu Liu,1 Guoqing Yin,1 Abdul-Quddus Mohammed,1 Xian Lv,1 Cailing Feng,1 Tingting Shi,1 Fuad A Abdu,1 Wenliang Che1,2 1Department of Cardiology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, Shanghai, People’s Republic of China; 2Department of Cardiology, Shanghai Tenth People’s Hospital Chongming Branch, Shanghai, People’s Republic of ChinaCorrespondence: Wenliang Che; Fuad A AbduDepartment of Cardiology, Shanghai Tenth People’s Hospital, Tongji University School of Medicine, 301 Yanchang Road, Jingan District, Shanghai, 200072, People’s Republic of ChinaTel +86-21-66307259Fax +86-21-66301051Email chewenliang@tongji.edu.cn; 1691026@tongji.edu.cnPurpose: The association of serum uric acid (SUA) levels with cardiovascular outcomes in patients with coronary artery disease (CAD) has been extensively studied and yielded conflicting results. We aimed to investigate whether the severity of coronary stenosis and ischemia influences the prognostic impact of SUA levels in patients with CAD undergoing D-SPECT.Patients and Methods: This study consecutively included patients who were admitted for CAD in Shanghai Tenth People’s Hospital between June 2014 and August 2018, had complete SUA data and underwent both coronary angiography and D-SPECT within 3 months. Hyperuricemia was defined as an SUA level of > 7 mg/dL in men and > 6 mg/dL in women. The primary outcome was major adverse cardiovascular events (MACE), defined as a composite of cardiac death, unplanned coronary revascularization, nonfatal myocardial infarction, ischemic stroke, heart failure, and angina-related hospitalization.Results: A total of 695 patients were included, of whom 432 (62.2%) presented with obstructive CAD and 117 (16.8%) had hyperuricemia. During a median follow-up of 26 months, the incidence rates of MACE in patients with hyperuricemia and normouricemia were 15.2% and 21.1%, respectively. After a multivariable adjustment, hyperuricemia was significantly associated with an increased risk of MACE (HR: 1.39, 95% CI: 1.03– 1.87, p = 0.033) when compared with normouricemia. When repeating the primary analysis in patients with and without obstructive CAD, we showed that hyperuricemia was independently associated with an 80% increased risk of MACE among patients with nonobstructive CAD (HR: 1.80, 95% CI: 1.04– 3.11, p = 0.035), while such a significant association was not found among those with obstructive CAD (HR: 1.18, 95% CI: 0.82– 1.72, p = 0.373). Moreover, we uncovered a U-shaped and linear trajectory of SUA levels with MACE in the obstructive and nonobstructive CAD, respectively. The sex-specific analysis showed that the adverse impact of hyperuricemia was only pronounced in males (HR: 1.73, 95% CI: 1.18– 2.53, p = 0.005) but not in females (HR: 0.98, 95% CI: 0.57– 1.66, p = 0.933).Conclusion: Hyperuricemia is significantly associated with increased risk of MACE in the nonobstructive CAD rather than in the obstructive CAD.Keywords: coronary artery disease, serum uric acid, D-SPECT, nonobstructive, outcomes